Health-related quality of life of dialysis patients during early COVID-19 lockdowns: a snapshot from a public hospital in Malaysia - Ganesh, Sritheran Paneerselvam; Goh, Khang Wen; Kassab, Yaman Walid; Muhammad Junaid, Farrukh; Goh, Bey Hing *; Lua, Pei Lin; Hermansyah, Andi; Long, Chiau Ming * (Frontiers Media, 2023)
Background End-stage renal disease is the last stage of chronic kidney disease and can affect the quality of life (QOL) of dialysis patients. The aim of this study was to assess the quality of life and examine its determinants.